PENGARUH PENYULUHAN DAN MEDIA POSTER TENTANG ANEMIA TERHADAP TINGKAT PENGETAHUAN DAN SIKAP PADA SANTRIWATI (Studi Di Pondok Pesantren Al-Bisyri Kota Semarang) - Aulia Medina Sulistyowati; M. Zen Rahfiluddin; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Health problems in the group of young women ages 12-19 years that are often encountered is anemia. The effects of anemia can cause ongoing stress and fatigue complications. The influencing factor is the lack of knowledge and attitudes of young women about anemia. Efforts to improve knowledge and attitudes in young women in anemia health problems can be through nutrition education. The purpose of this study was to determine the effect of nutrition education using posters on the level of knowledge and attitudes of adolescent female students. This research uses Pre-Experimental Design One Group with 36 research samples with purposive sampling technique. The research group was given a pre-test and then given nutrition education with Poster media, then post-test to be given after giving nutrition education with vulnerable time 2 weeks after being given a pre-test. The results showed that there was an increase in knowledge of the good category by 27.8% to 100% and an increase in attitude in providing good category interventions by 50% to 61.1%. Based on the Wilcoxon Signed Ranks Test and Paired t-test there are differences in the level of knowledge p = 0,001 (p <0.05) and there are differences in attitude p = 0,001 (p <0.05). The conclusion of this study is that there is an influence of nutrition education on increasing knowledge and attitudes about Adolescent Girls' Anemia. The suggestion of this research is the boarding school and the government should increase knowledge about nutrition for young women with anemia so that they can provide good attitudes and practices to be prevented by young women who have anemia.Keywords: Counseling, Poster, Anemia Knowledge, Anemia Attitude, Young Women